Impact Of Business Model Disclosure On The Value Relevance Of Accounting Information For Investors: Empirical Analysis - Abdul-Amir Zainy, Hussein Zuhair (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to test the impact of disclosure of the business model on the value relevance of accounting information for investors in the Iraqi banking sector. The pilot study was conducted on several Iraqi hotels in the Iraqi market for securities and the number of 8 hotels for the period 2016-2018, as this period was characterized by the adoption of international accounting standards and international financial reporting standards, and disclosure of hotels on their business model. the study found a set of results, the most important of which is that the Management Commentary framework indicators for IASB 2010 are the best indicators for the disclosure of the business model in the Iraqi banking sector, as well as that the business model disclosure works to enhance the relevance of the value of accounting information for investors, through the development of Ohlson 1995 model.